PENGUKURAN DAN PENGARUH KINERJA GURU RA (RAUDLATUL ATHFAL) BERPRESTASI - Fu`ad Arif Noor (Tunas Siliwangi, 2021)
This research was conducted to measure the performance of RA teachers with high performance and to determine the influence factors of their performance using a qualitative method with a psychological approach that was carried out directly on the subject under study, in order to obtain all data related to the performance of outstanding teachers. Data collection uses interviews, documentation, and observation. Data analysis techniques include reducing data, presenting, drawing conclusions and verifying. Data validity test is done by triangulation techniques.The research succeeded in revealing that the performance measurement of RA teacher achievement through six dimensions (namely: quality of work, speed/ accuracy, initiative in work, work ability and communication), as well as two strategies in developing the performance of RA teacher achievement (ie: training and performance motivation). Furthermore, there are two factors that affect performance, first internal factors within the individual teacher, in the form: physical (healthy body) and psychological (attention, intelligence, interests, motives, talents, readiness and maturity). These internal factors are N. Ach or Need for Achievement, which are drive, motive, or need for achievement. The two external factors, which are from outside the individual. This can be in the form of environmental conditions, ranging from the school environment, family, and community environment, to the facilities and infrastructure.